GP234 Thrombolysis of arterial ischaemic stroke in an eight month old: the first irish case. (June 2019) - Enright, Noelle; Melody, Laura; Barrett, Michael; Rea, David; O'Regan, Mary
Abstract : Paediatric arterial ischaemic stroke (AIS) is a potentially fatal condition with serious long term neurological sequelae. The rate of paediatric ischaemic stroke is 1.6 – 3.3 per 100, 000 and 61% of these children are left with long term neurological difficulties. Thrombolysis guidelines for children were introduced in May 2017 by the Royal College of Paediatrics and Child Health (RCPCH). However, these guidelines were developed for children from the age of eight and up, and may be used on a case by case basis for children from the age of two to eight years. There is very limited data on the use of thrombolysis in children of any age, particularly in the under two age group. Here we present the first case of AIS thrombolysis in an under two year old in Ireland. An eight-month old boy presented with a two-and-a-half-hour history of decreased movement of his left side. Importantly, his mother had noted the exact time symptoms commenced. His brain imaging showed a large right sided area of ischaemia in the territory of the middle cerebral artery (MCA), and a narrowed right internal carotid artery (ICA); no haemorrhage was seen. He was brought to intensive care and thrombolysis was commenced with alteplase and heparin. Methylprednisolone was also given as the narrowing of the ICA was felt to be inflammatory. Other investigations, including echocardiogram, homocysteine level, thrombophilia screen and varicella titres, were all negative. He has recovered well. He is back on full oral feeds and has learned to walk. He is right hand dominant, with no left sided neglect. He has no speech delay and has been discharged by both physiotherapy and occupational therapy. Enrolling children in randomised controlled trials to assess AIS treatment and outcomes remains extremely difficult, as evidenced by the Thrombolysis in Pediatric Stroke (TIPS) study, which was closed by the National Institute for Health (NIH) after only thrombolysing one patient despite recruiting 43. The issues centre on delays in presentation (usually outside the thrombolysis window), and in delayed recognition of AIS in emergency departments by clinicians. This case highlights the need for continued research in this area as it demonstrates that successful outcomes are possible after thrombolysis of AIS.